Using genetic algorithm in implementing capacitated vehicle routing problem - Mohammed M.A.; Ahmad M.S.; Mostafa S.A. (2023)
Vehicle Routing Problem (VRP) has been considered as a significant segment in logistic handling. Thus, a proper selection of vehicle routes plays a very important part to ameliorate the economic benefits of logistic operations. In this paper, we consider the application of a Genetic Algorithm (GA) to a Capacitated Vehicle Routing Problem (CVRP) in which a set of vehicles with limits on capacity and travel time are available to service a set of customers and constrained by earliest and latest time for serving. The results of our test show that GA is able to determine the optimum route for the vehicles while maintaining their constraints of capacity and travel time. 2012 IEEE.